The Evaluation of Debt Exchanges. (IMF Working Papers; Working Paper ;, 1990)
An approach is presented for analyzing debt-for-debt exchanges from the perspective of the exchange's impact on the country's contractual obligations and from the perspective of the creditors whose participation is sought. A general model is developed for valuing partially guaranteed debt instruments and an intuitive motivation is suggested for upper and lower bounds on the valuation of instruments carrying specific as well as rolling guarantees. An appendix presents several easily employed rules of thumb which have been suggested in the literature for valuing collateralized instruments and for estimating the possible net debt reduction achievable through their issuance.